The Influence of Explicit Instruction Learning Model toward 11th Grade Student’s Learning Outcomes - Sahade Sahade; Yunita Susan Amsa (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
This research aims to determine the influence of explicit instriction learning model toward 11th grade student‟s learning outcomes in accounting subjects at SMA Negeri 16 Makassar. The Variables in this research are explicit instriction learning model (X) and learning outcomes (Y). The population is the entire students of XI IPS clas at SMA Negeri 16 Makassar school 2016/2017 that consist of 147 students, while the sample determination uses purposive sampling technique with the number of sample is 36 students, technique of data collection used are test and observation. Technique of data analysis was done by using analysis of data validity and statistic analysis of SPSS 22 for windows. Based on the results of data analysis simple linear regression Y= -0.162+0,861X, where in every addition of one value of lerning model „explicit instruction‟, the lerning result incrased to 2.247. The mean score of pretest was 52 and posttest was 88.083 from the correlation coefficient of 0.247. Based on the t-test analysis, it was found that the tcalculation was 5.515 which was bigger than ttable 2.000. The R2 (R Square value was 0.247. The t-test result showed significant increase after treatment.